Ameliorating the Effects of Phytochemical Substances on the Setting of Cement with Rice Bran in the Production of Particle Boards Using a Natural Accelerator - Ogunkunle, Olaoluwa Ayobami; Olajide, Sunday Emmanuel (European Journal of Applied Sciences, 2023)
This research work evaluated the various means and alternatives that could be devised to improve the compatibility between rice bran and cement. Phytochemicals referred to as inhibitory substances, present in rice bran hinders its compatibility with cement via the means of compatibility factor obtained. The various ways that were looked into include the hot water treatment extraction process which reduced the intensity of water-soluble phytochemicals to an acceptable level and the addition of chemical additives. More so, cow horn (natural accelerator) - an appropriate naturally occurring calcium (Ca) source which is a cheap and effective substitute for the chemical additives was employed in improving compatibility factor. The existence and the extent of bonding in rice bran-cement bonded composites were also looked into. In order to compare the extent of compatibility, varying concentrations of chemical additives such as CaCl2, FeCl3, SnCl2 and SnCl4 were used with cow horn. These chemical additives act as accelerator as they decrease setting time. Thus, accelerating hydration reaction between the mineral binder used which is Portland cement and the rice bran.